Wireless subcutaneous trigeminal nerve field stimulation for refractory trigeminal pain: a single center experience - Hajiabadi, Mohammad Mehdi; Jakobs, Martin; Unterberg, Andreas; Ahmadi, Rezvan (Neuromodulation, 2021)
Introduction - Subcutaneous trigeminal nerve field stimulation (sTNFS) is a neuromodulatory treatment for neuropathic trigeminal pain with the ability to reduce the intensity and frequency of pain attacks. However, hardware issues including lead migration, skin erosion, infection, so-called pocket pain at the site of the implanted neurostimulator are reported. Implantable wireless neurostimulation technology promises not only an even less invasive sTNFS treatment and thinner and more flexible electrodes better suited for facial implants, but also provides further advantages such as lack of an implantable neurostimulator and 3T magnetic resonance imaging compatibility. - Material and Methods - All patients who had received trial stimulation with a partially implantable sTNFS system were analyzed for ICHD-3 (3rd edition of the International Classification of Headache Disorders) diagnosis, success of trial stimulation, pre- and postoperative pain intensity, frequency of attacks, complications, and side-effects of sTNFS. - Results - All patients (N = 3) responded to sTNFS (≥50% pain reduction) during the trial period. According to ICHD-3, N = 2 of the patients were classified with trigeminal neuralgia (TN) with concomitant persistent facial pain and N = 1 patient with multiple sclerosis associated TN. The time of the test period was 44 ± 31.24 days (mean ± SD). The average daily duration of stimulation per patient amounted 2.5 ± 2.2 hours (range 1-5). The pain intensity (defined on a visual analog scale) was reduced by 80% ± 17% (mean ± SD). Reduction or cessation in pain medication was observed in all patients. No surgical complications occurred in the long-term follow-up period of 18.84 ± 6 (mean ± SD) months. - Conclusion - The partially implantable sTNFS device seems to be safe, effective, and reliable. Compared to conventional devices, the equipment is not limited to the length of trial stimulation. Furthermore, the daily stimulation duration was much shorter compared to previous reports.